Operationalizing dominant mathematical representations in real analysis through an open ended diagnostic - Nursupiamin; Resnawati; Ikram, Muhammad; Rustan, Edhy; Rochaminah, Sutji; Sudarsana, I Wayan (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aims to develop an open-ended diagnostic test to identify pre-service mathematics teachers’ Dominant Mathematical Representations (DMR) in Real Analysis, with a specific focus on convergent sequences. Method: A Research and Development (R&D) approach was employed using Plomp’s development model, which includes preliminary research, prototyping, and assessment phases. The diagnostic instrument was constructed based on representational theory and consisted of six open-ended tasks designed to elicit representational choice, integration, and transferability. Content validity and linguistic clarity were evaluated by two mathematics education experts and one language expert. A limited field trial involving 19 pre-service mathematics teachers was conducted to examine the instrument’s validity and practicality. Data were collected through the diagnostic test, expert validation sheets, and a student response questionnaire, and analyzed descriptively using qualitative feedback and quantitative percentage-based indicators. Findings: The results indicate that the developed diagnostic test demonstrates strong content validity, with a mean validity score of 85.4%, classified as very valid. The practicality evaluation yielded a mean score of 83.7%, indicating that the instrument is very practical in terms of clarity, format, language, and time allocation. Expert review confirmed alignment between the test items and the DMR construct, while student responses indicated feasibility and comprehensibility. Significance: This study contributes to mathematics education assessment by operationalizing Dominant Mathematical Representations as an explicitly assessable construct through open-ended diagnostic tasks, providing a foundation for representation-sensitive instruction in Real Analysis.